Stroke - Lindley, Richard Iain (Oxford University Press, 2008)
In this book, a large amount of reliable research data has been summarised to provide an authoritative evidence based medicine guide to stroke definition, incidence, management and prevention. This book will be of great interest to those who have had a stroke or Transient Ischaemic Attack, and for those who are concerned about having a stroke. Students and healthcare professionals will find it a useful introduction to stroke medicine. The author, a leading professor of geriatric medicine and stroke expert, puts stroke in its public health context and emphasises that we already know a huge amount but have often failed to implement strategies to improve stroke care and prevent stroke in the first place